Acid–Base‐Controlled Stereoselective Metalation of Overhanging Carboxylic Acid Porphyrins: Consequences for the Formation of Heterobimetallic Complexes. Issue 33 (28th June 2013) - Le Gac, Stéphane; Najjari, Btissam; Dorcet, Vincent; Roisnel, Thierry; Fusaro, Luca; Luhmer, Michel; Furet, Eric; Halet, Jean‐François; Boitrel, Bernard
Abstract Overhanging carboxylic acid porphyrins have revealed promising ditopic ligands offering a new entry in the field of supramolecular coordination chemistry of porphyrinoids. Notably, the adjunction of a so‐called hanging‐atop (HAT) PbII cation to regular PbII porphyrin complexes allowed a stereoselective incorporation of the N‐core bound cation, and an allosterically controlled Newton's cradle‐like motion of the two PbII ions also emerged from such bimetallic complexes. In this contribution, we have extended this work to other ligands and metal ions, aiming at understanding the parameters that control the HAT PbII coordination. The nature of the N‐core bound metal ion (ZnII, CdII), the influence of the deprotonation state of the overhanging COOH group and the presence of a neutral ligand on the opposite side (exogenous or intramolecular), have been examined through 1H NMR spectroscopic experiments with the help of radiocrystallographic structures and DFT calculations. Single and bis‐strap ligands have been considered. They all incorporate a COOH group hung over the N‐core on one side. For the bis‐strap ligands, either an ester or an amide group has been introduced on the other side. In the presence of a base, the mononuclear ZnII or CdII complexes incorporate the carbonyl of the overhanging carboxylate as apical ligand, decreasing its availability for the binding of a HAT PbII. An allosteric effector (e.g., 4‐dimethylaminopyridine (DMAP), in the case of a single‐strap ligand) or an intramolecular ligand (e.g., an amide group), strong enough to compete with the carbonyl of the hung COO−, is required to switch the N‐core bound cation to the opposite side with concomitant release of the COO−, thereby allowing HAT PbII complexation. In the absence of a base, ZnII or CdII binds preferentially the carbonyl of the intramolecular ester or amide groups in apical position rather than that of the COOH. This better preorganization, with the overhanging COOH fully available, is responsible for a stronger binding of the HAT PbII. Thus, either allosteric or acid–base control is achieved through stereoselective metalation of ZnII or CdII. In the latter case, according to the deprotonation state of the COOH group, the best electron‐donating ligand is located on one or the other side of the porphyrin (COO−>CONHR>COOR>COOH): the lower affinity of COOH for ZnII and CdII, the higher for a HAT PbII. These insights provide new opportunities for the elaboration of innovative bimetallic molecular switches.